HAEMATOLOGICAL AND BIOCHEMICAL INDICES OF RED SOKOTO GOAT BREED (CAPRA AEGAGRUS HIRCUS) FED BROWSE’S PLANTS FEED FORMULATION - Ntagbu, Folashade G.; Aborisade, Wakili T.; Awe, S. (FUDMA JOURNAL OF SCIENCES, 2025)
The present study investigated the effect of different browse plant feed formulations on the haematology and serum biochemical indices of Red Sokoto Goat (Capra aegagrus hircus) breed. Fifteen (15) growing goats of average 8.60 ± 0.50 kg body weight were randomly allocated into five dietary groups in a completely randomized designed model with three (3) animals in each group. The control (T5) group was placed on a basal diet only while the remaining four groups were supplemented with Afzelia africana (TAa) Detarium microcarpum (TDm), Daniellia oliveri (TDo) and Khaya senegalensis (TKs). The studied lasted for fourteen (14) weeks.The chemical composition of crude protein CP (12.70 - 15.70 %) was similar (P>0.05) for all the treatments.The dry matter (DM) contents of the experimental diets varied between 92.70 and 94.40%.The haematology result showed that PCV (22.53 – 28.93 %), Hb (7.51 – 9.64g/dl), RBC (9.19 – 18.77 x 1012), MCV (10.64 -17.53 fl), MCH (1.24 – 2.04 pg), and MCHC (33.32 – 33.33g/dl) were not significantly affected (P>0.05) in all the dietary treatments, except for WBC (8.38 – 13.51 x 109) which were significantly affected (P<0.05) in all the treatments. The lowest mean values (22.53%, 7.51 (g/dl), 9.19 x 1012, and 1.24 pg) were recorded in the control (T5) diet for PCV, Hb, RBC, and MCH, respectively, as against the supplementary diet (T1-T4) treatments. The results of the glucose, total protein, and cholesterol recorded were significantly affected (P<0.05) in all the dietary treatments except for albumin, globulin, creatinine, and urea, which were...